Analisis Penerapan Fungsi Manajemen Poac Dalam Pelaksanaan Acara Ephics 2.0 - Fitriatunnisa Shabrina; Riyanto Wibowo (Nawasena: Jurnal Ilmiah Pariwisata, 2024)
Event management is the application of project management that is specifically engaged in the process of making and developing personal events or group events, associations, formal agencies and informal agencies with varying scales. In event management, there is time management, management, and human resources (HR) involved, resulting in a function that is responsible for planning, organizing, controlling, and evaluating elements. In supporting learning on campus, students are required to carry out an event commonly called Entrance of Portal to Hospitable International Competitions & Seminars (EPHICS). The event is an application of the theory learned in class. As a form of student creativity in realizing the management of Event Management in the Hospitality Sector. The implementation of the EPHICS 2.0 program is the result of the collaboration of students of the D4 Convention & Event Management Study Program together with D4 Hospitality Management through recruitment activities as a support in the concept of study program collaboration, with the involvement of students who play the role of organizers directly at the EPHICS 2.0 event, a forum is created as a place for creativity that has the potential to get a lot of attention from the community. In this study, the author wants to conduct research in analyzing the POAC Management Function in the Implementation of EPHICS 2.0 Events